Digital Culture and Using Social Media Posts in Foreign Language Learning - Irina-Ana DROBOT (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
The purpose of the paper is to show how technology can be used to make attractive the learning of a foreign language. Social media posts about vocabulary in various foreign languages, for instance, as well as short conversational phrases, could be used to replace the traditional drill types of exercises. Videos that are present could be used to replace the traditional listening exercises. The social media posts could be used as additional material to what is used during class. It is assumed that social media is part of students’ lifestyle, and that learning foreign languages is adapted to modern life.